О ПОНЯТИИ «НЕСОВЕРШЕННОЛЕТНИЕ» И ЗАЩИТЕ ИХ ПРАВ В ГРАЖДАНСКОМ СУДОПРОИЗВОДСТВЕ АЗЕРБАЙДЖАНСКОЙ РЕСПУБЛИКИ - МАМЕДЛИ, Сабина (SUPREMANCE OF LAW, 2016)
The article discusses the concept of «minors» in the civil area. We investigate the legal status of minors in the process of protecting their rights and interests in civil proceedings of the Azer-baijan Republic. It is proved that after independence in 1991 the Republic of Azerbaijan has completely transformed its legislation to international law which are directed. Also considered such international instruments as the Geneva Declaration of the Rights of the Child 1924 Declaration of the Rights of the Child in 1959, the International Convention on the Rights of the Child of 1989, the World Declaration on the Survival, Protection and Development of Children in 1990, the Declaration and Plan of Action «A World Fit for life children «and some of the other rules and principles. All these documents are re-flected in the Constitution, the Family Code, Civil Code, Code of Civil Procedure.